MARKET information systems and agricultural commodity exchanges: Strengthening Market Signals and Institutions: synthesis report - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
This consultation was expected to identify key factors that have supported success, and to discuss issues related to new opportunities for strengthening market signals...